Calculating effective dose in PET/CT scan using MCNP code and MIRD phantom (Damascus University Journal for engineering sciences, 2022)
The idea of measuring biological and biochemical processes in vivo was put forward in the thirties of the last century when industrially produced radionuclides such as carbon, nitrogen, and oxygen were discovered, which decompose by emitting external radiation that can be captured and photographed using PET devices.In this research, we will review the most important radionuclides used in PET scintigraphy, in addition to measuring the dose of internal organs in the body when using PET scintigraphy using the computer phantom MIRD and the MCNP code for brain PET/CT scan resulting from 18F-FDG (18F-2-deoxy-D-glucose)Results:  From study, we found that the maximum effective dose value when combined with PET/CT scans is in the brain region 0.418 mSv, and in the thyroid gland 0.419 mSv, followed by the skin region of the head and neck where the effective dose is 0.362 mSv, then the chest region 0.331 mSv.
Keywords: PET/CT scan; MCNP code, MIRD phantom; effective dose